2008
DOI: 10.1088/0268-1242/23/12/125025
|View full text |Cite
|
Sign up to set email alerts
|

GaN thermal decomposition in N2AP-MOCVD environment

Abstract: Undoped GaN layers were grown on SiN-treated (0 0 0 1) sapphire substrates by atmospheric pressure metal organic chemical vapor deposition (AP-MOCVD). The thermal decomposition of GaN layers was studied by in situ laser reflectometry and scanning electron microscopy (SEM) analysis. The thermal annealing process was performed in the MOCVD vertical reactor in the temperature range 900-1200 • C in N 2 atmosphere. It was observed that annealing at temperature above 1100 • C causes the decomposition of GaN layers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…It is shown in the figure that the area where the temperature is higher than the threshold temperature (nearly 1300 K) tends to be concentrated on the surface. [ 36,37 ] This is consistent with the experimental and simulated results in the reported literature. We also conclude that only the GaN, which is very close to the interface (about 50 nm deep), will be heated to over 1000 K during the LLO process.…”
Section: Resultssupporting
confidence: 91%
“…It is shown in the figure that the area where the temperature is higher than the threshold temperature (nearly 1300 K) tends to be concentrated on the surface. [ 36,37 ] This is consistent with the experimental and simulated results in the reported literature. We also conclude that only the GaN, which is very close to the interface (about 50 nm deep), will be heated to over 1000 K during the LLO process.…”
Section: Resultssupporting
confidence: 91%
“…Several studies showed that the annealing of GaN at temperature beyond 1000 °C even in nitrogen causes decomposition in the near GaN surface region [12][13][14]. In previous works, we demonstrated that GaN decomposition starts from critical temperature beyond 700 °C under H 2 and 1100 °C under N 2 [15][16][17]. Bchetnia et al [17] studied the annealing temperature on GaN decomposition rate in the range of 1000-1200 °C under N 2 environment in AP-MOVPE reactor.…”
Section: Introductionmentioning
confidence: 80%
“…In previous works, we demonstrated that GaN decomposition starts from critical temperature beyond 700 °C under H 2 and 1100 °C under N 2 [15][16][17]. Bchetnia et al [17] studied the annealing temperature on GaN decomposition rate in the range of 1000-1200 °C under N 2 environment in AP-MOVPE reactor. The GaN thermal decomposition has been studied by others groups versus several parameters that relates to decomposition environment such as temperature, pressure, carrier gas and geometry reactor [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 97%
“…observed that annealing at temperatures above 1100 °C causes the decomposition of GaN layers in an N 2 atmosphere at atmospheric pressure. 21 In the case of the GaN film with a pre-deposited liquid Ga droplet, noticeable decomposition started after annealing at 720 °C for 15 min in flowing Ar + H 2 at 1 bar. The surface became rougher and small holes appeared near the Ga-GaN boundary.…”
Section: Theoretical Foundation and Design Of The Htap Templatementioning
confidence: 99%
“…15 After annealing at temperatures over 1100 °C in an N 2 atmosphere, the GaN film began to decompose and it had a porous-like surface with a non-uniform distribution of pore size. 21 Y. Oshima et al proposed a VAS (void-assisted separation) technique for separating freestanding GaN from sapphire substrates with the assistance of numerous small voids. 8 In the VAS method, a thick GaN layer grown by HVPE was spontaneously separated as a result of thermal stress at a boundary consisting of numerous voids generated around a thin porous TiN layer inserted between the thick GaN layer and the base substrate during the cooling process after the growth of freestanding GaN wafers from the sapphire substrate with the assistance of numerous small voids.…”
Section: Theoretical Foundation and Design Of The Htap Templatementioning
confidence: 99%